The dynamic impacts of financial development and human capital on CO2 emission intensity in China: an ARDL approach - Li, Peng; Ouyang, Yaofu (Journal of Business Economics and Management, 2019)
This paper studies the dynamic impacts of financial development, human capital, and economic growth on CO2 emission intensity in China for the period 1978–2015, with a structural breakpoint in 1992, by employing an autoregressive distributed lag (ARDL) approach. The estimations show that there exists a long-run cointegration linkage among the variables, with three main findings. First, financial openness measured by net FDI inflows can significantly reduce CO2 emission intensity in both the short-term and the long-term, whereas the effects of both financial scale and financial efficiency are limited and insignificant. Second, there exists an inverted N-shaped relationship between human capital and CO2 emission intensity: improving human capital first decreases CO2 emission intensity (before 1992), then increases it in the short-run (after 1992), and, finally, lessens it in the long-run. Last, raising per capita income can also significantly lower CO2 emission intensity in the long-run. Accordingly, some policy implications are also discussed.